Circuit analysis on the inductance evolution based on electrical signal from various type plasma focus device - Mohamad, Saiful Najmee; Ismail, Fairuz Diana; Ahmad Noorden, Ahmad Fakhrurrazi; Haider, Zuhaib; Ali, Jalil (Melville, NY, 2017)
Numerous configurations of plasma focus devices (PFD) have been introduced around the globe. The distinct electrode configuration of the PFD will give out different inductance profile. A circuit analysis has been done to study on the significant difference between the inductance evolution in a coaxial discharge based on various published results of PFD. The discharge current signal, tube voltage and current derivative of the particular shots from distinct PFD was digitized and analyze. The investigation was piloted for three different types of PFD. It was observed that there is a significant difference for the normalize inductance profile during the discharge between the individual PFD with different electrode configuration. The depletion of the radial start current with the normalised inductance development for Mather type (PF-1000) is found to be 25.9% from static discharge. The current depletion continues to drop 1.1% and 1.3% more for a Spherical type (PNK-13) and Filippov type (PF-3) respectively.